2020
DOI: 10.32479/ijefi.9591
|View full text |Cite
|
Sign up to set email alerts
|

Terrorist Activities, Investor Sentiment, and Stock Returns: Evidence From Pakistan

Abstract: Motivated by the previous literature on investor sentiment and assuming that terrorist activities affect investor mood, this study attempts to address the psychological impact of terrorism for investors in Pakistan stock market. Apart from a direct economic loss, major terrorist incidents create/ exacerbate uncertainty and fear in the market. The investors are likely to over-respond to such incidents and once the dust settles the market tend to recover. The analysis of cumulative abnormal returns in the afterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Research conducted by Siswantoro (2020) found that there was a significant difference in the TVA variables of hotel, restaurant, and tourism sub-sector stocks. Another study with a similar result was conducted by Ali et al (2020) who tested the impact of the terrorist incidents on the Pakistan stock exchange. It was concluded that the event has affected investor sentiment and confidence because there was a significant trading volume activity difference before and after the event.…”
Section: The Effect Of Emergency Ppkm Policy Announcement On Trading ...mentioning
confidence: 79%
“…Research conducted by Siswantoro (2020) found that there was a significant difference in the TVA variables of hotel, restaurant, and tourism sub-sector stocks. Another study with a similar result was conducted by Ali et al (2020) who tested the impact of the terrorist incidents on the Pakistan stock exchange. It was concluded that the event has affected investor sentiment and confidence because there was a significant trading volume activity difference before and after the event.…”
Section: The Effect Of Emergency Ppkm Policy Announcement On Trading ...mentioning
confidence: 79%
“…This result aligns with the studies of Caldara and Iacoviello (2018) and Salisu et al (2022), which also report that threats of GPRs impacted more on the market than actual realization or occurrence of these risks. Similarly, from the analysis of cumulative abnormal returns in the aftermaths of terrorist incidents, Ali et al (2020) provide strong evidence that the terrorist incidents adversely affect investors' sentiments and confidence in the market as manifested through relatively feeble trading volumes. Recent studies such as Eldor and Melnick (2004), Farooq and Ahmed (2008), Kollias et al (2010, 2011), Wijeweera (2015), Narayan et al (2018), and Khan et al (2020) involving different countries that are prone to some of the components of GPRs, such as terrorist attacks, political tension, and war, have demonstrated the broad and destructive effects of GPRs on investors' confidence with effects on the performance of stock, forex, and money markets.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Here, we formulate an empirical model that examines the impact of GPR on GFCy. There are already numerous studies analyzing the relationship between GPR and financial assets especially stocks, on the basis of the risk-return hypothesis and other portfolio management theories (see Ali et al, 2020;Apergis et al, 2017;Balcilar et al, 2018;Bouras et al, 2019;Brounen & Derwall, 2010;Chen & Siems, 2004;Chesney et al, 2011;Hoque & Zaidi, 2020;Hui, 2020;Narayan et al, 2018;Yang et al, 2021). We construct a predictive model that connects high-risk events to investment in risky assets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study recommends that the government focus on equipping young people with useful skills to engage them in constructive activities. Ali, Qingshi, Memon, Baz, & Ali (2017) explored the impact of different terrorist attacks on the Pakistan Stock Exchange. Their study utilized a model that incorporates the effects of new and good news on changing volatility.…”
Section: Empirical Reviewmentioning
confidence: 99%